The role of input flood and input enhancement in EFL learners’ acquisition of collocations - Szudarski, Paweł; Carter, Ronald (Wiley, 2016)
The study investigated L2 learners’ acquisition of verb-noun and adjective-noun collocations following two kinds of instruction: input flood only and input flood plus input enhancement (in the form of underlining). L1 Polish learners of English as a foreign language were exposed to infrequent collocations embedded in stories that were read during three consecutive weeks. Their collocational competence was subsequently assessed in a battery of delayed tests tapping into productive and receptive levels of collocational mastery. Input flood plus input enhancement resulted in the acquisition of collocations but only at the level of form recall and form recognition. The findings are discussed with reference to the complexity of acquiring and measuring L2 collocational knowledge. The article concludes with implications for instructed second language acquisition.